Testing of the Seismic Gap Hypothesis in a Model With Realistic Earthquake Statistics. Issue 6 (26th May 2022) - Petrillo, G.; Rosso, A.; Lippiello, E.
Abstract: The seismic gap hypothesis states that fault regions where no large earthquake has recently occurred, are more prone than others to host the next large earthquake. It can lead to the idea of immunity after local disaster which, notwithstanding it sounds reasonable, it has been frequently rejected by objective testing. More generally, the estimate of the occurrence probability of the next big shock on the basis of the time delay from the last earthquake still represents a big challenge. The problem is that this issue cannot be addressed only on the basis of historical catalogs which contain too few well documented big shocks, and decades of future observations appear necessary. On the other hand, recent results have shown that important insights can be obtained from the spatial organization of aftershocks and its relationship to the mainshock slip profile. Here, we address this issue by monitoring the stress evolution together with the occurrence of big shocks and their aftershocks in a model where the fault is described as an elastic interface embedded in a ductile medium. The model reproduces all relevant statistical features of earthquake occurrence and allows us to perform accurate testing of the seismic gap hypothesis and its consequences, particularly on the side of aftershock spatial patterns. We show that large earthquakes do not regularly repeat in time, but it is possible to achieve insights on the time until the next big shock from the percentage of aftershocks occurring inside the mainshock slip contour. Plain Language Summary: The seismic gap hypothesis states that large earthquakes preferentially occur in seismogenic fault regions, accordingly termed gap regions, where no large earthquake has been observed for a long time. The validity of the hypothesis implies that it is possible to achieve some insights on the timing of the next large earthquake on the basis of the previous seismic history. However, since the 1990s numerous statistical tests have failed to support this hypothesis and the current state of art is that many scientists consider the occurrence of large earthquakes fully unpredictable. In our study, we investigate the validity of the seismic gap hypothesis in a theoretical model which reproduces the main statistical features of real seismic occurrence in space, time, and magnitude. We show that, even if the model assumes a homogeneous and constant stress rate, the occurrence of large shocks is very irregular in time and space. Nonetheless, our findings support the hypothesis that an accurate monitoring of the shear stress rate on the fault and of previous seismic activity can be useful to identify the regions which have a higher probability to host the next big shock. Key Points: We investigate the hypothesis of alternation in a physical model of a seismic fault presenting realistic features of aftershock occurrence Aftershocks do not occur in large‐slip areas which become relocked and the next mainshock occurs in different fault regions The time until the next big shock is inversely proportional to the percentage of aftershocks inside the mainshock slip contour